2017
DOI: 10.1038/s41598-017-05095-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of positive and negative allosteric modulation in metabotropic glutamate receptors 4 and 5 with a dual ligand

Abstract: As class C GPCRs and regulators of synaptic activity, human metabotropic glutamate receptors (mGluRs) 4 and 5 are prime targets for allosteric modulation, with mGlu5 inhibition or mGlu4 stimulation potentially treating conditions like chronic pain and Parkinson’s disease. As an allosteric modulator that can bind both receptors, 2-Methyl-6-(phenylethynyl)pyridine (MPEP) is able to negatively modulate mGlu5 or positively modulate mGlu4. At a structural level, how it elicits these responses and how mGluRs undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 82 publications
4
22
0
Order By: Relevance
“…by "a" according to Ballesteros-Weinstein scheme (Ballesteros and Weinstein, 1995)] for class A GPCRs or followed by "c" according to Pin et al (2003) scheme for class C GPCRs). Despite previous studies have proposed functional similarities between class A GPCR micro-switches and certain non-homologous class C GPCR residues (Perez-Benito et al, 2017; Llinas Del Torrent et al, 2019) their respective conformational changes have been observed only in MD simulations of mGlu receptor homology models, but not in mGlu receptor crystal structures (Dore et al, 2014;Christopher et al, 2015;Koehl et al, 2019) or in MD simulations starting from those (Feng et al, 2015;Dalton et al, 2017;Perez-Benito et al, 2017;Llinas Del Torrent et al, 2019). Furthermore, while the outward movement of TM6 is a hallmark of class A GPCR activation, the extent of this movement is noticeably lower in mGlu5 even when enhanced sampling methods are employed (Cong et al, 2019).…”
Section: Figure 1 | (A)mentioning
confidence: 91%
See 4 more Smart Citations
“…by "a" according to Ballesteros-Weinstein scheme (Ballesteros and Weinstein, 1995)] for class A GPCRs or followed by "c" according to Pin et al (2003) scheme for class C GPCRs). Despite previous studies have proposed functional similarities between class A GPCR micro-switches and certain non-homologous class C GPCR residues (Perez-Benito et al, 2017; Llinas Del Torrent et al, 2019) their respective conformational changes have been observed only in MD simulations of mGlu receptor homology models, but not in mGlu receptor crystal structures (Dore et al, 2014;Christopher et al, 2015;Koehl et al, 2019) or in MD simulations starting from those (Feng et al, 2015;Dalton et al, 2017;Perez-Benito et al, 2017;Llinas Del Torrent et al, 2019). Furthermore, while the outward movement of TM6 is a hallmark of class A GPCR activation, the extent of this movement is noticeably lower in mGlu5 even when enhanced sampling methods are employed (Cong et al, 2019).…”
Section: Figure 1 | (A)mentioning
confidence: 91%
“…In particular, a region was detected (blue circle, top of Figure 3) which includes a critical point that appears to identify a higher-energy "pseudo-stable" receptor state. It could be hypothesized that this region corresponds to an active-like receptor conformation on the basis that separation of intracellular loops is predicted to be a necessary feature of mGlu receptor activation (Dalton et al, 2017). Interestingly, the PMF whose collective variable involves the explicit breaking of the Lys665-Glu770 ionic lock did not show any clear minimum along its trajectory.…”
Section: Figure 1 | (A)mentioning
confidence: 99%
See 3 more Smart Citations